Bibliometric Mapping of Research Developments Using Qardh Financing Topics On Google Scholar Using Vosviewer - Parman Komarudin; Muhammad Sodiki; Imro Atut Toyyibah; Syahrani Syahrani; Zakiyah Zakiyah (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
Al-Qardh is a bailout or loan for people who need fast funds, one of the bank's services in serving the community, apart from kafalah, hiwalah and others. This study aims to determine the development of research publications within a period of 13 (thirteen) years, determine the direction of qardh financing research trends, identify the relationship between scientific concepts, and find out the knowledge network of qardh financing based on keywords (co-occurrence) and author collaboration ( co-authorship). The method used in this study is descriptive bibliometric analysis, the data used was taken from 2010-2022. Data collection was carried out based on the Google scholar database with the keyword qardh financing and additional supporting keywords including Qardhul Hasan, soft loans, Islamic financing, Islamic banking, with a publication limit of 1000 journals. Data collection was carried out using Publish or Perish (PoP) software as metadata. Data analysis was performed using Vosviewer software as a medium for bibliometric analysis. The results of the study show that in the last 13 years, the number of publications regarding qardh financing research indexed by Google Scholar has fluctuated, but in terms of quantity it has increased significantly.